THE ROLE OF KEMKOMDIGI IN ADDRESSING PIRATED VIDEO GAME DOWNLOAD SITES - Nicholas Pratama Budi Eryono; Andriyanto Adhi Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Video game piracy through illegal download sites has become a serious issue that harms game developers and publishers, particularly concerning their copyright and economic rights. This research aims to analyze the role of the Ministry of Communication and Digital (Kemkomdigi) in addressing these sites, based on Law Number 28 of 2014 on Copyright and Law Number 11 of 2008 on Electronic Information and Transactions (ITE). The research method employed is normative legal research with a statutory and regulatory analysis approach. The results of the study indicate that Kemkomdigi plays a role in blocking access to piracy sites after receiving recommendations and reports from the Ministry of Law and Human Rights. However, challenges such as bureaucratic chains, lack of inter-agency coordination, and low public awareness continue to hinder the effectiveness of handling Illegal Video Game Download Sites. Kemkomdigi has developed the Content Moderation Compliance System (SAMAN) to enhance detection and blocking of illegal content. Long-term solutions to tackle piracy include public education, strengthening inter-agency cooperation, and advancing blocking technologies to create a digital environment free from piracy.